Intensive dysphagia rehabilitation program for patients with head and neck cancer. Issue 3 (18th November 2021) - Charters, Emma; Clark, Jonathan
Abstract: Background: In response to the pathophysiology and expected trajectory of dysphagia that arises following treatment for head and neck cancer (HNC), an intensive and progressive approach to dysphagia is warranted. This pilot study evaluates the recovery of swallowing function following the implementation of an exercise‐based approach to dysphagia rehabilitation. Methods: Consecutive recruitment was carried out prospectively at a quaternary referral centre. Participants were aged 18 years and older and had completed treatment for HNC. Dysphagia was assessed pre and post a 10‐week rehabilitation program using videofluoroscopy swallow study (VFSS) and clinician‐and patient‐reported outcomes. Results: Ten participants were recruited over a 6‐month period, all of whom had oropharyngeal dysphagia confirmed on VFSS. At the conclusion of the 10‐week intervention period, DIGEST (Dynamic Imaging Grade of Swallowing Toxicity) scores improved significantly for both safety and efficiency components. Four of seven participants who had a percutaneous endoscopic gastrostomy tube at baseline were no longer reliant on it for their nutrition, hydration or medication at the completion of the therapeutic period. While four participants continued to aspirate on thin fluids, none developed aspiration pneumonia. Conclusion: Oropharyngeal dysphagia as a consequence of HNC treatment is challenging to rehabilitate; however, in selected patients, it is responsive to intensive and individualized rehabilitation programs. Abstract : This study describes the novel trismus device combined with an intensive trismus rehabilitation program for patients with head and neck cancer.